Shield Equipment Optimization and Construction Control Technology in Water-Rich and Sandy Cobble Stratum: A Case Study of the First Yellow River Metro Tunnel Undercrossing - Fei Ye; Nan Qin; Xiang Gao; Xue-yong Quan; Xian-zhuo Qin; Bing Dai (Advances in Civil Engineering)
The Lanzhou Yellow River Tunnel is the first metro shield tunnel that undercrosses the Yellow River in China. It was completed after successfully overcoming several construction challenges, including strata with a high proportion of large-sized sandy cobble stratum being saturated, large-scale sand pits along the bank of the Yellow River, and a combination of boulders and erratic blocks of rock. Given the difficulties in constructing the tunnel, this paper summarizes the scheme employed to transform the cutter and cutter head design to be applicable to sandy cobble stratum and the key technology used to form the slurry film to facilitate crossing the sand pits in a systematic way. The transformation scheme primarily involved the addition of an adjusting device to control the aperture ratio of the shield on the cutter head, a protective device for the hob hub, and a protective device for the piston rod in the oil cylinder of the crusher. The implementation of measures mentioned above guarantees the safe completion of the tunnel, which can provide a reference for similar projects.